Influence of Aqueous Extract of Emblica officinalis Fruits on Tolbutamide Induced Hypoglycemia/Antihyperglycemia in Normal and Diabetic Rats - Eswar Kumar, K.; Sreekanth, N.; Mastan, S.K. (Asian Journal of Chemistry, 2010)
This work reports the evaluation of the influence of aqueous extract of Emblica officinalis fruits on tolbutamide activity in normal and diabetic rats. Tolbutamide produced hypoglycemic activity in a dose dependent manner in normal and diabetic condition. In the presence of Emblica officinalis fruits, tolbutamide produced early on set of action and maintained for longer period compared to tolbutamide group. An aqueous extract of Emblica officinalis fruits was found to improve tolbutamide response in normal and diabetic rats.